The Guidelines for Business Operation Development in the Digital Age of the Film and Video Industries in Thailand - Dathpong, Waranya; Phanniphong, Kanakarn; Sombat, Paneepan (Arts of Management Journal, 2024)
The research on the guidelines for business operation development in the digital age of the film and video industries in Thailand has the following objectives: 1) To study the factors influencing the development of business operations in the digital age of the film and video industries in Thailand. 2) To create a structural equation model of the factors influencing the development of business operations in the digital age of the film and video industries in Thailand. The study focuses on a sample group of business entrepreneurs in film and video production activities, consisting of 400 companies. The data is analyzed using structural equation modeling. The research adopts a mixed-methods approach, combining quantitative and qualitative methods. The research tools include questionnaires and in-depth interviews. The quantitative research found that: 1) Six factors, namely information technology, learning orientation, external environment, innovation capability, organizational agility, and balanced scorecard, significantly influence the development directions of business operations in the digital era of the film and television production industry in Thailand. 2) The structural equation model developed by the researchers aligns with observational data according to specified criteria: 2/df =1.729, P-Values = 0.736, CFI = 0.994, GFI = 0.976, RMSEA = 0.049, RMR = 0.021. The qualitative research found that business operations in the digital age of the film and video industries, with six studied factors, are crucial for driving organizational success in the film and television production industry. Importantly, every company is willing to embrace various changes, strategically plan to cope with different situations, and retain skilled personnel to ensure continued business operations.